Code-Switching in IsiXhosa Music: A Mechanism for Language Preservation or Shift? - Izu, Benjamin Obeghare; Somlata, Zakhile (Fakultas Ilmu Budaya, Universitas Mulawarman, 2025)
Code-switching, the alternation between two or more languages within a discourse, is a prevalent linguistic phenomenon in multilingual societies. In South Africa, where English often coexists with indigenous languages such as isiXhosa, music has become a key medium for linguistic and cultural expression. This qualitative research paper examines the role of code-switching in Xhosa music, specifically analysing Amanda Black’s song Kutheni Na featuring Kwesta, to determine whether such linguistic alternations contribute to language preservation or language shift. Using discourse analysis, this study looks at how isiXhosa, English, and isiZulu are used together in the song's lyrics, looking at the language patterns and the sociocultural reasons for these choices. The analysis is framed by Myers-Scotton’s Markedness Model, Fishman’s Domain Theory, and Critical Discourse Analysis (CDA) to assess the implications of code-switching for Xhosa preservation or shift. Findings indicate that code-switching in Kutheni Na serves expressive and functional purposes. While this interplay of language fusion in the song helps sustain isiXhosa in contemporary music, the growing use of English in South African music is worrying. It might lead to people gradually preferring English in mainstream discourse, which could cause shifts in language use over time.